From Chloroplast Biogenesis to Chlorophyll Accumulation: The Interplay of Light and Hormones on Gene Expression in Camellia sinensis cv. Shuchazao Leaves - Liu, Linlin; Lin, Ning; Liu, Xuyang; Yang, Shu; Wang, Wei; Wan, Xiaochun (Frontiers in Plant Science, 2020)
Chloroplast development and chlorophyll metabolism have been well described in model plants but not in perennial woody crops. Of particular interest is the interplay between light and hormones under shade conditions. We report that the shade induced accumulation of chlorophylls in Camellia sinensis cv. Shuchazao leaves is at least as a result of (a) positive changes in chloroplast development and (b) light/hormonal regulation of genes and transcription factors involved in the chlorophyll biosynthesis pathway. Under shade conditions, leaves developed an abundance of enlarged chloroplasts encapsulating more prominent thylakoid membranes. Four major metabolites in the chlorophyll biosynthesis pathway namely Chl a, Chl b, DPP, and Mg-Proto IX increased under shade conditions while PBG decreased significantly. Significant changes were found at the transcription level of regulators of chloroplast biogenesis (GLK1 and LHCB), the structural genes in the chlorophyll biosynthesis pathway (HEMA1, CLH1, PORA, and CAO) and potential components involved in light signaling (PHYA, CRY1, HY5, and DELLAs). Two central signal integrators (GLK1 and LHCB) between the nucleus and chloroplast showed clear responses to shade, suggesting a crucial role of light in regulating chloroplast development in tea leaves. Concurrent with the changes in gene expression, the concentrations of endogenous phytohormones (auxin, cytokinin, and gibberellins) increased significantly in the later stages of shade conditions. Two key integrators involved in the hormone signal pathways, EIN3 and EBF1/2, increased under shade conditions suggesting that shade induced changes to hormone levels may play some role in modulating chlorophyll biosynthesis in the tea leaves. Overall, this data suggests that the light and hormone influence over chloroplast development and chlorophyll biosynthesis in Camellia is similar to that of Arabidopsis. This study provides new insights into the molecular mechanisms that regulate chlorophyll biosynthesis in response to light and hormones in a commercially important woody plant such as Camellia, which may facilitate the breeding of high-chlorophyll tea cultivars for the improvement of sensory features of the green tea product.